Socio-economic determinants affecting the lifestyle of pregnant women - Fatemeh Estebsari; Farideh Jalili-Bahabadi; Camelia Rohani; Zahra Rahimi Khalifeh Kandi; Davoud Mostafaei (Iranian Association of Health Education and Health Promotion, 2020)
Background and Objective: Lifestyle is one of the factors influencing health. The lifestyle of pregnant women undergoes many changes during pregnancy and childbirth. The aim of this study was to identify socio-economic determinants affecting the lifestyle of pregnant women. Materials and Methods: This was a descriptive-analytic study carried out on 300 pregnant women in Yazd who were selected by random sampling. Data collection tools include demographic information questionnaire and HPLPII profile. Data were entered into SPSS 18. Descriptive and analytical statistics were used for analysis. Significant level was <0.05. Results: The mean score of health promoting behaviors of pregnant women was 154.9 ± 2.2. The highest mean score belonged to the spiritual growth dimension (30 ± 3.6) and the lowest mean belonged to the physical activity dimension (17.8 ± 10.2). According to the results, there was a significant relationship between age, education and employment of pregnant women and education of spouse with health promoting behaviors (P <0.05). Conclusion: Based on the results of the present study, demographic, social and economic variables have an effect on the lifestyle of pregnant women and attention to it should be considered as a priority in planning related to providing health services and macro-national policies to improve maternal and children health should be considered